2012
DOI: 10.1258/ijsa.2012.011444
|View full text |Cite
|
Sign up to set email alerts
|

Testicular microlithiasis: is it significant?

Abstract: Previously considered to be a benign finding on scrotal ultrasonography, testicular microlithiasis (TM) is now recognized as a condition associated with the development of testicular neoplasia. Despite this the management of TM remains unclear. We review the evidence for this association and suggested management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…11,12 Pooled data from 15 published studies of 33 549 ultrasound examinations give an overall prevalence of 2.7% in adult males. 13 The sonographic appearances of TM were first reported in the late 1980s 14 and are characterized by the presence of small (1-3 mm), non-shadowing, echogenic foci that are diffusely or focally distributed within the testicular parenchyma ( Figure 1); the condition is usually, but not always, bilateral. TM has been subdivided into "classical" and "limited" forms depending on whether there are more or less than five microliths on any single ultrasound image; 15 however, this arbitrary subdivision does not appear to have any prognostic value.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11,12 Pooled data from 15 published studies of 33 549 ultrasound examinations give an overall prevalence of 2.7% in adult males. 13 The sonographic appearances of TM were first reported in the late 1980s 14 and are characterized by the presence of small (1-3 mm), non-shadowing, echogenic foci that are diffusely or focally distributed within the testicular parenchyma ( Figure 1); the condition is usually, but not always, bilateral. TM has been subdivided into "classical" and "limited" forms depending on whether there are more or less than five microliths on any single ultrasound image; 15 however, this arbitrary subdivision does not appear to have any prognostic value.…”
Section: Discussionmentioning
confidence: 98%
“…6 Pooled data from 15 studies involving 752 symptomatic males with TM showed that 17.2% had a co-existent testicular tumour with TM conferring a relative risk of between 13.2 and 36.5 for the presence of a TGCT. 13 It is unsurprising, therefore, that many authorities have recommended a variety of management strategies-regular self-examination, clinician-based examination, ultrasound surveillance, tumour marker surveillance and testicular biopsy-despite a lack of evidence proving a causal association. Evidence linking TM with TGCT remains largely based on case reports and retrospective series, introducing potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a clear association between microlithiasis and testicular cancer, particularly in patients with risk factors such as cryptorchidism, Down's syndrome, testicular atrophy, infertility, and family history of testicular cancer [2]. However, neither follow-up nor self-examination is recommended in patients with microlithiasis without any risk factors because there are no benefits from them [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…TML has been suggested a premalignant condition (1,2224). In our study, TML and normal testicles showed no clinical relevant difference in ADC values, indicating that TML testicles may have the same mechanical properties as normal tissue.…”
Section: Discussionmentioning
confidence: 99%